Acute pancreatitis associated with cholera (Indian Journal of Case Reports, 2019)
Acute Pancreatitis (AP) is the inflammation of the pancreas, common causes being gall stones, alcohol, iatrogenic and trauma. Infections, mainly viral, are a rare cause of acute pancreatitis, mainly reported as case reports or series in the literature. Cholera caused by Vibrio Cholera, though rare these days, is characterized by vomiting and profuse watery diarrhea. We present an interesting case of Cholera complicated by mild pancreatitis with no other obvious cause following admission which was managed conservatively with full recovery. We are highlighting an unheard complication of cholera.